Soil and climatic influence on the free and glycosidically bound volatiles of grapes from two white varieties from vinhos verdes region - Araújo, Isabel M. (2004)
The Vinhos Verdes Region is situated in the northwest of Portugal. The Atlantic Ocean and the relief markedly influence the climate. This region is in Viticultural Zone C I a) of the Winegrowing Regions of the European Communities. The produced wine is unique and its specific characteristics are mainly due to the climate and soil. The white Vinho Verde is softly alcoholic, with a delicate, fresh and fruity bouquet. In this work we investigated the influence of the climate and the soil on the volatile compounds of grapes from two autochthonous white grape varieties, Alvarinho and Loureiro, in two sub-regions for each one of them (Alvarinho - Monção and Lima; Loureiro - Lima and Cávado). The research was carried out during three years: 1996, 1997 and 1998. We found out that the global characteristics of the grapes from the two varieties depend on the harvest factor (climate) rather than on the sub-region where the vine is planted. The characteristics of the soil have an even lesser influence on the variableness of the samples, although the Alvarinho variety picked in the Lima sub-region seems to have different characteristics.